2021
DOI: 10.1038/s41598-021-02221-2
|View full text |Cite
|
Sign up to set email alerts
|

FLT3-ITD transduces autonomous growth signals during its biosynthetic trafficking in acute myelogenous leukemia cells

Abstract: FMS-like tyrosine kinase 3 (FLT3) in hematopoietic cells binds to its ligand at the plasma membrane (PM), then transduces growth signals. FLT3 gene alterations that lead the kinase to assume its permanently active form, such as internal tandem duplication (ITD) and D835Y substitution, are found in 30–40% of acute myelogenous leukemia (AML) patients. Thus, drugs for molecular targeting of FLT3 mutants have been developed for the treatment of AML. Several groups have reported that compared with wild-type FLT3 (F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…While PTPRJ is presumed to be primarily localized at the plasma membrane ( 37 , 46 , 83 ), FLT3 ITD is retained in its immature HM form in the ER/Golgi system ( 17 , 66 ). The maturation efficiency of FLT3 ITD has been demonstrated to be inversely correlated to its tyrosine phosphorylation ( 17 , 66 ). PTP such as SHP1 and PTP1B have been found to dephosphorylate FLT3 ITD ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While PTPRJ is presumed to be primarily localized at the plasma membrane ( 37 , 46 , 83 ), FLT3 ITD is retained in its immature HM form in the ER/Golgi system ( 17 , 66 ). The maturation efficiency of FLT3 ITD has been demonstrated to be inversely correlated to its tyrosine phosphorylation ( 17 , 66 ). PTP such as SHP1 and PTP1B have been found to dephosphorylate FLT3 ITD ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, FLT3 ITD mutations presumably disrupt the auto-inhibitory activity of the JM domain ( 4 , 5 ), leading to ligand-independent dimerization, auto-phosphorylation, and constitutive activation of the receptor ( 10 , 11 , 14 ). In contrast to the wt receptor and due to its constitutive kinase activity, ITD-mutated FLT3 is predominantly retained in the endoplasmic reticulum (ER) and Golgi compartments ( 15 17 ), from where it strongly promotes activation of signal transducer and activator of transcription 5 (STAT5) ( 15 17 ). Due to a residual pool of FLT3 ITD reaching the plasma membrane, constitutive activation of AKT and extracellular signal-regulated kinases 1/2 (ERK1/2) signalling can also be found ( 16 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the FLT3-ITD accumulates in the Golgi area in AML cells, similarly to KIT in GIST cells 19 . However, PKD2 knockdown in the AML cell line, MOLM-14, did not affect FLT3 levels, signals, or mutant localization (Figures S8A and S8B).…”
Section: Loss Of Function Of Pkd2-related Machinery Does Not Affect R...mentioning
confidence: 91%
“…In sharp contrast, during biosynthetic trafficking in GIST cells, the KIT Ex17 mutant and KIT Ex11 accumulate in the Golgi/trans-Golgi network (TGN) area, where they initiate oncogenic signaling [16][17][18] . We further showed that FLT3-internal tandem duplication (FLT3-ITD) in AML triggers growth signals in the Golgi area and the endoplasmic reticulum (ER) 19 . Although the organelles where RTK accumulates differ among cancer types, compartment-dependent signaling is a characteristic feature of mutant RTKs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation